The Best American Short Stories 1979 - Oates, Joyce Carol 1938- (Boston Houghton Mifflin Company, 1979)
Short stories of 1979.
Include Bibliography and Notes
Includes the Yearbook of the American short story.
Keywords: Short stories, American -- Short stories, Canadian -- American fiction